The Development of E-Atlas Learning Media Based on Mobile Learning on Cells Structure Material in SMA N 1 Kandangserang - Setiawati, Diah Agung; Setiati, Ning; Pribadi, Tyas Agung (Journal of Biology Education, 2019)
Cells are the one of hard-to-understand material for students, because it cannot be seen directly by students therefore it requires detailed visualization of images to explain the structure and processes that occur in it. Adequate visualization is needed to study better the structure and function of cells. This is the reason why we need to develop a mobile learning media. The media is an E-atlas of cell structure and function. This product is then analyzed its suitability as a learning media in SMA N 1 Kandangserang. Students of classes XI MIA 1 and XI MIA 2 academic year 2018/2019 were selected as the samples of this research using saturated sampling techniques. This is a research and development (R & D). Research shows that E-atlas is suitable as learning media. E-atlas affects the learning outcomes, where the N-gain value shows an increase with an average of 0.72 (categorized as high) with classical completeness of 83%. It is concluded that E-atlas mobile learning is suitable as a teaching learning medium for students.